Accounting for account-abilities: Examining the relationships between farm nutrient measurement and collaborative water governance dynamics in Canterbury, New Zealand - Hale, James; Legun, Katharine; Campbell, Hugh (Journal of rural studies, 2022)
Water quality has become a significant concern for the New Zealand public. The source of its decline in recent years has been largely attributed to the expansion of the dairying industry, and its improvement, a focal point of environmental management. A collaborative model has been developed in the Canterbury region, where committees have been created including government representatives, water management experts, farmers, and non-farming community members. These committees develop water management plans in a water catchment and can be seen to embody a form of socialising accountability where different groups hold each other accountable and share responsibility. One feature of the plans is the establishment of nitrogen loss thresholds for farms in a catchment, implemented through a highly technical form of nutrient modelling. Drawing from interviews and observations in Canterbury water governance networks, we argue that there is a tension between collaborative forms of environmental governance that seeks to socialise accountability, and nutrient modelling that de-socialise accountability in practice. We discuss how these tensions may challenge participatory forms of governance. •Develops an analytic approach to examine processes of accountability and legitimation in governance practice.•Argues there is a tension between collaborative governance that socialises accountability, and modelling that de-socialises accountability.•Discusses tensions between individualising processes of accountability and collectivising forms of governance.